The use of ustekinumab in a patient with severe psoriasis and positive HBV serology - Raquel Bissacotti Steglich; Luana Pizarro Meneghello; André Vicente Esteves de Carvalho; Hugo Cheinquer; Fernanda Melo Muller; Flávia Pereira Reginatto (Sociedade Brasileira de Dermatologia, 2014)
Psoriasis is a chronic inflammatory, immune-mediated disease that affects 1% to 2% of the world's population. Immunobiological medications are prescribed for certain patients with severe forms of psoriasis, however, these drugs increase the risk of reactivation of viral diseases such as hepatitis B. We report the case of a patient with severe psoriasis with positive serology for the Hepatitis B virus, who received ustekinumab (a human monoclonal antibody against interleukin 12 and 23). In this patient, the use of ustekinumab did not reactivate the Hepatitis B virus. Given the high prevalence of chronic viral infections in patients who are candidates for biologic therapy, as well as the potential for reactivate chronic viral illness, randomized controlled studies are needed to assess the risks and benefits of such therapy in these populations.